(Re)constructing an Early Medieval Irish Ard - Brendan O`Neill; Claus Kropp; Frank Trommer; Vanessa Töngi (EXARC Journal, 2022)
This article outlines the results of an EXARC funded 2019 Twinning project exploring the production and use of an Irish early medieval ard. In this, the project partners researched the evidence for early ploughs and ards, made bloomery iron, produced an ard share, and worked wood to form the frame of the ard. This paper also includes the results of scientific analysis and reflections on ploughing using specially trained draft animals. Ultimately, this provided details about this crucial agricultural technology and its place within early medieval society. This project is also a case-study, showcasing collaborative, practical research strengths between leading centers for experimental archaeology.